2014
DOI: 10.1007/s00894-014-2367-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics study of H + DBr and D + HBr reaction

Abstract: Time-dependent quantum wave packet calculations have been performed for the H + DBr and D + HBr reaction using the recent diabatic potential energy surfaces. Reaction probabilities, integral cross sections, and rate constants are obtained. The results show that the isotopic effects have an influence on the nonadiabatic effect which is generally inversely proportional to the atom mass. The calculated rate constants are in good overall agreement with experimental values, indicating that the ab initio surfaces ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…The total reaction integral cross section (ICS) from a specific initial state is computed by summing the reaction probabilities over all relevant partial waves σ υ 0 j 0 τ false( E normalc false) = 1 false( 2 j 0 + 1 false) K 0 ε π k 2 J t o t K 0 ( 2 J t o t + 1 ) P υ 0 j 0 τ K 0 J t o t ε false( E normalc false) where k = 2 μ E c and μ is the reduced mass between the reactants. The differential cross section (DCS) can, in principle, be computed from the S -matrix elements, but the calculation of the latter involves complex coordinate transforms and is rarely attempted beyond tetratomic systems. ,<...…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total reaction integral cross section (ICS) from a specific initial state is computed by summing the reaction probabilities over all relevant partial waves σ υ 0 j 0 τ false( E normalc false) = 1 false( 2 j 0 + 1 false) K 0 ε π k 2 J t o t K 0 ( 2 J t o t + 1 ) P υ 0 j 0 τ K 0 J t o t ε false( E normalc false) where k = 2 μ E c and μ is the reduced mass between the reactants. The differential cross section (DCS) can, in principle, be computed from the S -matrix elements, but the calculation of the latter involves complex coordinate transforms and is rarely attempted beyond tetratomic systems. ,<...…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…While a quantum mechanical treatment of the reactive scattering is preferred, the numerical cost of such calculations quickly becomes unaffordable as the size increases . As an inexpensive alternative, quasi-classical trajectory (QCT) methods have been widely applied to study reactions. , In the QCT approach, the atomic coordinates and momenta of reactants are prepared in specific quantum states using ad hoc quantization conditions, and the subsequent classical dynamics on the PES is followed by solving the Hamilton’s equations.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 However, HNTs have large specic surface area, high van der Waals force and low concentration of polar functional groups on the external surface, this properties lead to poor dispersion and weak interfacial interaction in epoxy/HNTs matrix, which deteriorate the mechanical properties of the epoxy nanodielectrics. [26][27][28][29][30][31] Although the chemical functionalization of HNTs is considered as one of the most easy ways among the various methods to apply in designing a good compatibility toward to epoxy resins, as well as other physicochemical properties, [31][32][33] the mass production in term of quantity, quality and cost has been one of the biggest challenges while considering the extremely high cost and complex chemical process in preparation of the functionalization HNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] Excellent characteristics of HNTs result in great mechanical and thermal properties, providing applications for preparing HNTs/polymer nanocomposites. [ 23‐25 ] Cavallaro et al [ 26 ] prepared Mater‐Bi/halloysite composite materials by using the solvent casting method. It revealed that the strongest enhancements of the thermal stability and tensile properties were achieved at 10 wt% of Mater‐Bi/halloysite.…”
Section: Introductionmentioning
confidence: 99%